2021
DOI: 10.1145/3449170
|View full text |Cite
|
Sign up to set email alerts
|

Vartalaap

Abstract: Air pollution is a global challenge for cities across the globe. Understanding the public perception of air pollution can help policymakers engage better with the public and appropriately introduce policies. Accurate public perception can also help people to identify the health risks of air pollution and act accordingly. Unfortunately, current techniques for determining perception are not scalable: it involves surveying few hundred people with questionnaire-based surveys. Using the advances in natural language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The pollution levels are the lowest during the monsoon months, but not negligible. This cyclical nature also overlaps with the overall interest in the topic and efforts to address the issue, peaking at the start of the winter pollution episodes, with the most the media coverage (based on the number of articles published), public interest (based on social media activity and google search trends), and political will (based on the number of political statements made) [12,13].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The pollution levels are the lowest during the monsoon months, but not negligible. This cyclical nature also overlaps with the overall interest in the topic and efforts to address the issue, peaking at the start of the winter pollution episodes, with the most the media coverage (based on the number of articles published), public interest (based on social media activity and google search trends), and political will (based on the number of political statements made) [12,13].…”
Section: Introductionmentioning
confidence: 94%
“…After the transport sector, the source with the most media coverage is the open burning of agricultural waste in October and November to prepare fields for the winter crop in the states of Punjab and Haryana [12,13]. Due to time constraints and the lack of an affordable and wide-scale residue management system, farmers consider burning the residue a faster and cheaper way than tilling and inundating the fields to mulch the waste naturally over weeks [98,99].…”
Section: Agricultural Waste Burningmentioning
confidence: 99%
“…In India, an analysis of the print media and the social media reports suggests that the increase in the public complaints 80 on air pollution coincides with the release of open data from the Embassy stations in 2015 in Delhi and Mumbai (Adhikary et al, 2021;Patel et al, 2022). A significant rate of increase in the total number of monitoring stations operating and reporting information in India, also matched this event.…”
Section: Ambient Monitoring Data Videos and Mass Mediamentioning
confidence: 88%
“…They also say that the public response (tweets) is driven by relative PM 2.5 levels experienced by the people rather than absolute values. Another public sentiment study (Adhikary et al 2021) on air pollution mitigation measures found the people's response to be mixed, and those policies were highly criticized. Hswen et al (2019), Sailunaz and Alhajj (2019), Lu et al (2022)used natural language processing techniques to extract and classify sentiment/emotion from the social media posts.…”
Section: Sentiment Analysis Studiesmentioning
confidence: 99%